CERITA ARJUNA WIWAHA DIVISUALKAN DALAM BENTUK RELIEF WAYANG BEBER PADA MEDIUM SELONGSONG PELURU - Yoga Pradana Aditya Putra; Basuki Teguh Yuwono (TEXTURE : Art and Culture Journal, 2018)
ABSTRACTThe story of Arjuna Wiwaha is visualized in the form of metal reliefs using the main material of bullet casings and supported by additional materials. Arjuna Wiwaha story is a story that tells the journey of Arjuna alienated to Cave Indrakila, to undergo tapa brata with the aim of asking for directions and ask the magic weapons to God. Until the crowning of Arjuna became King with the title of King Kariti and married to seven angels for seven days at Heaven.The character in Arjuna Wiwaha’s story on this work is the result of the transformation of the shadow puppet face shape with the Beber puppet, became the new character of the Beber puppet character and focused on the main character. The main materials used in the manufacture of this final project are bullet shell (brass metal), brass plate, copper plate, copper pipe and supported by additional material. In its embodiment, This final project works using several workmanship techniques and some finishing techniques.Keywords: Arjuna Wiwaha, Beber Puppet, Bullet Cartridges